FIQH MAQASHID AL-KHITHAB: MUHAWALAT AL-'UTHUR 'ALA MAFHUM AL-MUSAWAH FI-SYAHADAT RAJUL WA-IMRAATAYN - Husni Mubarrak (State of Islamic Institute Langsa, 2020)
This article examines the problem of the diversity of interpretations of the testimony of two women equal to the testimony of one man in surah Al-Baqarah, verse 282. A number of interpretations that have surfaced use the hujjah, naqliy or aqliy, to reinforce the view that the testimony of two women is equal to one man. Some even return it to the verse of ta'abbudiy (unthinkable), so it does not open alternative interpretations because the verse is understood as final. By using the concept of